'When elephants battle, the grass suffers.' Power, ivory and the Syrian elephant. (3rd May 2016) - Çakırlar, Canan; Ikram, Salima
Abstract : The craftsmanship of the ivory objects in Late Bronze Age and Iron Age Eastern Mediterranean leave no doubt as to their intention to impress. Elephant teeth are an important raw material for the manufacture of these objects. Zooarchaeological research shows that cranial, dental, and postcranial remains of Asian elephants ( Elephas maximus ) are nearly as ubiquitous as worked ivory across Southwest Asia. This paper attempts to reconstruct the origins, habitat, range, life style and the end of the Syrian elephant. It discusses recent bone and tooth finds of this animal from Kinet Höyük and Tell Atchana in the Hatay in Turkey against the background of previous research on the 'Syrian elephant' and ivory production in the Levant. It confirms the proposal that Asian elephants were not endemic to the region and that their arrival was anthropogenic. The Syrian elephant was the product of the power-hungry Bronze Age elite in the region. Having become an 'evolutionarily significant unit' for centuries, these elephants died out in the 8th or 7th century BC. Present evidence, including off-site evidence, suggests that while their local extinction was also anthropogenic, elephants themselves were not merely passive victims in the process; they have made an already difficult and degraded environment even more unsustainable for themselves and the human communities in the region. The immense demand for ivory and competition among first commercial, then territorial powers of the Bronze Age Levant, who symbolically associated themselves with elephants, caused the birth of the 'Syrian elephant'. In their demise, not only the elites, but also non-elite herders and agriculturalists were probably responsible.